ILLOCUTIONARY ACTS ON PRESIDENT OBAMA’S ELECTION NIGHT SPEECH - Lasmaria Netty Kristiina; Ambalegin Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2019)
The research design of this study is descriptive qualitative. The data sources of this research are “Transcript of President Obama’s Election Night Speech” which is taken from the internet. The transcript is written by Federal News Service. This paper merely focuses on analyzing the most dominant types of Speech Actss on Transcript of President Obama’s Election Night Speech. This Transcript File of Federal News Service is analyzed by the perspective of Searl’s theory. From the analysis of audio file entitled “Transcript of President Obama’s Election Night Speech” it can be found four types of Searle’s illocutionary actss: Directive, commisive, representative and expressive. There are 33 data of illocutionary actss which consist of : 3 data are the type of Directive: 3 data showing request, 12 data of the type of Commisive: ten data is showing a promising and 2 data showing offering,11 data of the type of Representative: 7 data showing of asserting, 1data showing of concluding, and 1 data showing describing. 8 data of the type of Expressive: 7 data showing the thanking and 1 data showing apologizing. From the classification of the data, it can be seen clearly that the type of commisive is the most dominant. This was used since the President as a speaker want to declare the promising about future America during the reign in front of American people.